E-062 Impact of angiographic appearance of proximal middle cerebral artery occlusion on first pass reperfusion. (4th August 2020) - Mohammaden, M; Haussen, D; Pisani, L; Al-Bayati, A; Belagaje, S; Bhatt, N; Frankel, M; Nogueira, R
Abstract : Background and Purpose: The first pass effect (FPE) is a key predictor of clinical outcome after mechanical thrombectomy (MT) for large vessel occlusion stroke (LVOS). We aim to study the impact of initial angiographic appearance of middle cerebral artery (MCA) occlusion on FPE. Methods: A prospectively maintained MT database from January 2018 to December 2019 was reviewed. Patients with M1 segment MCA occlusion were included. FPE was defined as complete reperfusion (mTICI2c-3) after a single pass thrombectomy. Occlusion site angiographic appearance was classified into two categories; regular, when the occlusion is smooth stump with abrupt cut off and irregular which included all other types of occlusion. The primary outcomes were the rates of FPE and functional independence (90-day mRS 0–2). Uni- and multivariable analyses were performed to identify predictors of FPE. A secondary analysis was the interaction between the first line MT technique and the shape of occlusion on the FPE. Results: A total of 319 were included in the analysis, the mean age was 65.1 years, 168 (52.7%) were females. Median [IQR] baseline NIHSS score was 17 [12–21] and ASPECTS was 8 [7–9]. Patients with the regular shape of occlusion had a significantly higher frequency of smoking (28.5% vs. 18.5%, p=0.037). Cardioembolic strokes were more frequently presented with the regular shape of occlusion (53.1% vs. 43.9%). Conversely, intracranial atherosclerosis was significantly associated with irregular shape of occlusion (13.2% vs. 6%), p=0.04. Irregular occlusion shape had significantly lower median number of MT passes to achieve successful reperfusion (1 [1–2] vs. 2 [1–3], p=0.01 and higher rates of FPE 46% vs. 34.6%, p=0.04) and a trend to lower rates of parenchymal hematoma type 2 (2.6% vs. 6.9%, p=0.067). There was no significant interaction between first-line MT technique and the shape of occlusion on FPE. Functional independence and 90-day mortality were similar between the two groups. On multivariable analysis, the irregular shape of occlusion was an independent predictor of FPE (OR 1.756; 95% CI[1.049–2.940], p=0.03). Conclusions: The angiographic shape of M1 occlusion is a predictor of FPE. Large prospective multicenter studies are warranted for a better understanding of whether the occlusion appearance guides the selection of the MT techniques and hence potentially increase the chance of FPE. Disclosures: M. Mohammaden: None. D. Haussen: 2; C; Stryker, Vesalio. 4; C; Viz.AI. L. Pisani: None. A. Al-Bayati: None. S. Belagaje: None. N. Bhatt: None. M. Frankel: None. R. Nogueira: 2; C; Phenox, Anaconda, Genentech, Brainomix, Viz-AI